Identification of inhibitors of myeloid-derived suppressor cells activity through phenotypic chemical screening - Schröder, Matthias; Umansky, Viktor (OncoImmunology, 2017)
Tumors are infiltrated by cells of the immune system that interact through complex regulatory networks. Although tumor-specific CD8+ T cells can be found in peripheral blood and tumor samples from cancer patients, their function is inhibited by immunosuppressive cells such as regulatory T cells, tumor-associated macrophages, and myeloid-derived suppressor cells (MDSC). Recent clinical successes have demonstrated that alleviating immunosuppression and T cell exhaustion translates into long-term clinical benefits. Although tremendous progress has been achieved, tools that afford unbiased approaches and screenings to uncover new potential inhibitors or gene targets are lacking. In this study, we describe a system based on immortalized progenitors that allows straightforward investigation of myeloid cells. We show that bone marrow progenitors immortalized through the transduction of NUP98-HOXB4 transgene can be differentiated into CD11b+Gr-1+ MDSC that express Arginase-1 and PD-L1, produce reactive oxygen and nitrogen species, and suppress T cell function in vitro. To uncover chemical probes that interfere with MDSC biology, we performed a chemical phenotypic screening and identified 3-deazaneplanocin A as a novel modulator of MDSC functions. We characterized and compared the effect of 3-deazaneplanocin-A and all-trans retinoic acid, a well-known modulator of MDSC activity, on the expression of effector molecules and immunosuppressive functions of MDSC. Altogether, this proof-of-principle opens new possibilities for the identification of drugs targeting myeloid cells with immunosuppressive activities.